A novel blue-greenish emitting phosphor Ba3LaK(PO4)3F:Tb3+ with high thermal stability. (April 2016) - Zeng, Chao; Huang, Hongwei; Hu, Yingmo; Miao, Shihai; Zhou, Jun
Highlights: The Ba3 LaK(PO4 )3 F:Tb 3+ phosphors exhibit a broad excitation band. The Ba3 LaK(PO4 )3 F:Tb 3+ emission color adjust from blue to green. The Ba3 LaK(PO4 )3 F:Tb 3+ show superior thermal stability. Graphical abstract: Abstract: Ba3 La1− m K(PO4 )3 F: m Tb 3+ ( m = 0.01–0.50) phosphors have been prepared by a traditional high temperature solid-state reaction. XRD analysis verified the apatite-type phase structure of the as-prepared samples, and the morphology has been checked by the Scanning electron microscope (SEM). The emission spectrum of Ba3 LaK(PO4 )3 F:Tb 3+ phosphor consists of two regions, blue emission band from 380 to 470 nm and green emission band from 470 to 650 nm. With increasing Tb 3+ ions doped concentration ( m ), the color hue of Ba3 La1− m K(PO4 )3 F: m Tb 3+ adjusts from blue to green. On the basis of concentration quenching method, the critical distance between Tb 3+ ions is calculated to be 7.98 Å, suggesting that multipolar interaction predominate in quenching process. In addition, the temperature-dependence PL spectra of Ba3 LaK(PO4 )3 F:0.01Tb 3+ and Ba3 LaK(PO4 )3 F:0.40Tb 3+ phosphor are given, which exhibit superior thermal stability.